Pengaruh Pelatihan Kerja, Kompensasi Dan Iklim Organisasi Terhadap Kepuasan Kerja Pegawai - Subhan, Abdu; Isma, Fauzi Muliawan; Nazar, Nurul Khairy; Bukit, Sri Deviulina Br; Utama, Gita Pradana; Setiawati, Dewi; Wasesa, Supar; Supriadi, Supriadi (Graha Mitra Edukasi, 2024)
This study aims to determine the effect of work training, compensation and organizational climate partially and simultaneously on the employee job satisfaction in the Kantor Pelayanan Pajak Pratama Medan Belawan. The study was conducted at the Kantor Pelayanan Pajak Pratama Medan Belawan Jalan KL Yos Sudarso Km 8,2 Nomor 27 Medan, with a population of 98 people, and a study sample. of 96 people. The data analysis technique used is multiple regression analysis using the IMB Statistics computer program for Product and Service Solution (SPSS) version 24. Based on the analysis results obtained work training have a positive and significant effect on the employee job satisfaction of the Kantor Pelayanan Pajak Pratama Medan Belawan, this is supported by the results of t count analysis > t-table (5,483 > 2,011) at n = 96 at 95% significance level. Compensation has a not effect on the employee job satisfaction of the Primary Tax Service Office of Medan Timur, this is supported by an analysis of t count > t-table (3,007 > 2,011) at n = 96 at 95% significance level. Organizational climate has a not effect on the employee job satisfaction of the Kantor Pelayanan Pajak Pratama Medan Belawan, this is supported by an analysis of t count <-table (0,096 < 2,011) at n = 96 with a significant level of 95%.Value of F-count> F table (18,716 > 2,70) This states that together (multiple) there are positive and significant effects of work training, compensation and organizational climate on the employee job satisfaction of employees of the Kantor Pelayanan Pajak Pratama Medan Belawan. Thus the hypothesis proposed is accepted by the truth.